2018
DOI: 10.14740/gr942w
|View full text |Cite
|
Sign up to set email alerts
|

Aquanet Bowel Cleansing Device Versus Oral Sodium Picosulfate for Pre-Endoscopy Bowel Preparation: Propensity Score Analysis for Interventional Effectiveness Evaluation

Abstract: BackgroundColonoscopy procedures are commonly performed and have high success rates. However, poor or inadequate bowel preparation is one of the most common reasons for a repeated or failed colonoscopy. We therefore performed an observational study followed by propensity score modeling to evaluate and compare the quality of bowel preparation with the use of Aquanet bowel cleansing devices (BCDs) versus the use of oral sodium picosulfate solution.MethodsWe performed a prospective cross-sectional study to compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Regarding safety issues, there seem to be fewer side effects in patients undergoing CHT compared to oral preparation with cathartics. This is in line with the results of other studies of colonic irrigation in the form of colon hydrotherapy 8 9 10 11 12 13 14 15 16 17 32 . No AEs were recorded during the present study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Regarding safety issues, there seem to be fewer side effects in patients undergoing CHT compared to oral preparation with cathartics. This is in line with the results of other studies of colonic irrigation in the form of colon hydrotherapy 8 9 10 11 12 13 14 15 16 17 32 . No AEs were recorded during the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Colonic irrigation as an alternative method has been reported and was described as safe, effective and well tolerated. In addition, bowel cleansing quality of colonic irrigation is considered comparable to oral purgative regimes but with less side effects and high patient satisfaction 8 9 10 11 12 13 14 15 16 17 . Furthermore, colonic irrigation in the form of colon hydrotherapy is described by Parekh et al as the “future direction of bowel preparation” 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Using mechanical bowel cleansing before or during colonoscopy is proposed as an alternative to oral laxatives in selected patient groups. 103 , 104 , 105 , 106 , 107 Preprocedural devices work through retrograde bowel lavage using pressurized water one hour before colonoscopy, 108 , 109 , 110 while intraprocedural devices can be used during colonoscopy providing water‐pressured cleansing. 107 , 111 , 112 , 113 Feasibility studies have shown a clear potential, with adequate bowel preparation achieved in 97.9–100% and 68.8–91.1% of patients in whom intraprocedural devices 107 , 111 , 112 , 113 or preprocedural devices, 108 , 109 , 110 respectively, were used.…”
Section: Discussionmentioning
confidence: 99%
“…103 , 104 , 105 , 106 , 107 Preprocedural devices work through retrograde bowel lavage using pressurized water one hour before colonoscopy, 108 , 109 , 110 while intraprocedural devices can be used during colonoscopy providing water‐pressured cleansing. 107 , 111 , 112 , 113 Feasibility studies have shown a clear potential, with adequate bowel preparation achieved in 97.9–100% and 68.8–91.1% of patients in whom intraprocedural devices 107 , 111 , 112 , 113 or preprocedural devices, 108 , 109 , 110 respectively, were used. Nonetheless, the use of intraprocedural devices adds significantly to the total procedure time, and preprocedural devices require a specialized nurse to operate the system.…”
Section: Discussionmentioning
confidence: 99%
“…In the choice of intestinal cleansers, polyethylene glycol is still the most widely used at home and abroad [18], and recent metaanalysis shows sodium picosulfate/magnesium citrate with better tolerability and less frequent adverse events demonstrated non-inferior bowel cleaning efficacy than that of the polyethylene glycol [19]. In addition to active oral intestinal laxative preparations, in recent years, passive intestinal cleaning methods such as Aquanet EC-2000 have also been developed, with effects similar to oral sodium matrine sulfate and mannitol oral solutions [20,21]. In actual clinical work, the preparation situation is not optimistic.…”
Section: Discussionmentioning
confidence: 99%